Selenium in human and animal nutrition and need for selenium fertilization of crops - PRASAD, RAJENDRA; SINGH SHIVAY, YASHBIR (The Indian Journal of Agricultural Sciences, 2022)
Selenium is an essential micronutrient for humans and animals, required to increase immunity, protect cells from free radical damage and inflammation, and support a healthy metabolism. The typical manifestations of selenium deficiency in humans are loss of appetite, fatigue after even mild exercise, cardiac arrhythmia and palpitations, cardiac insufficiency, cardiomegaly, and congestive heart failure, swelling in the joints of arms and legs in children aged 5–13 years resulting in structural shortening of the fingers and long bones resulting in growth retardation and stunting. Clinical signs of selenium deficiency in cattle include mastitis, perinatal death and abortions, suboptimal fertility in adult cattle and suboptimal milk production, acute nutritional muscular dystrophy in young calves, sudden collapse or death of calves within 2–3 days of birth, stiff-legged gait, weakness and inability to stand or walk in young calves.Being a micronutrient for humans and animals, the margin between deficiency and toxicity of selenium are small and selenium supplementation has to be carefully planned. Agronomic biofortification by fertilizing crops on selenium deficient soils is the safest way and has been successfully tried in China and Finland. It is now practised in Australia and several other countries. However, the research work on selenium in soils, plants, animals and humans is of recent origin in India and needs utmost attention and priority considering its importance in the food chain.